Shoulder Muscular Activation during Common Kettlebell Exercises: A Randomized Cross-Sectional Surface EMG Study - Paköz, Büşra; Işiklar, Çağdaş; Turgut, Elif (Taylor & Francis Inc, 2026)
Purpose This study aimed to examine shoulder muscle activation patterns within functionally similar upper-body exercise categories performed using different resistance modalities. Methods Twenty healthy males (mean age 22.6 +/- 1.69 years) performed overhead pressing, rowing, and swinging tasks using kettlebells, dumbbells, and elastic bands. Surface electromyography (EMG) was used to record activity from seven shoulder muscles. The recorded electromyographic signals were normalized to maximal voluntary isometric contractions (%MVIC), log-transformed, and analyzed using a two-way repeated-measures analysis of variance (ANOVA) with exercise and muscle as within-subject factors. Results A repeated-measures ANOVA on log-transformed EMG data showed significant main effects of exercise (F(2.10, 39.95)=22.04, p<.001, eta(2) p=.537) and muscle (F(4.49, 85.34)=47.55, p<.001, eta(2) p=.714), as well as a significant exercise & times;muscle interaction (F(8.16, 154.98)=82.84, p<.001, eta(2) p=.813). Within the overhead pressing category, the Bottoms-Up Kettlebell Overhead Press elicited significantly greater activation than the traditional Kettlebell Overhead Press in the upper trapezius, lower trapezius, biceps brachii, and infraspinatus (all p<.050), with upper trapezius activation reaching 30.4 +/- 13.4%MVIC. In the rowing category, middle and lower trapezius activation was greater during free-weight rowing than during elastic band rowing, while serratus anterior activation remained relatively low across the rowing conditions. In the swing category, activation patterns were largely comparable between the two-hand kettlebell and dumbbell swings, whereas the one-hand kettlebell swing produced greater activation in selected muscles, with the lower trapezius showing the highest activation. Absolute between-exercise differences in %MVIC were modest. Conclusion Kettlebell, dumbbell, and elastic band exercises elicit distinct shoulder muscle activation profiles. These findings may inform exercise selection and program design when targeting specific shoulder muscles within task-oriented training contexts.
Keywords: Scapular Recruitment; Upper-Body Exercises; Overhead Stability; Resistance Modalities; Neuromuscular Activation